INTERNAL RESTRUCTURING AS A MEANS OF INCREASING INFORMATION SECURITY WHEN CODING DATA IN A STATISTICAL SPACE - Barannik, Vladimir; Tupitsya, Ivan; Barannik, Valery; Babenko, Yurii; Zhuikov, Dmytro; Yroshenko, Valerii (Ukrainian Information Security Research Journal, 2023)
In order to improve the efficiency of statistical data coding from the standpoint of increasing the data security of an information resource, a fundamentally new approach to restructuring is proposed - internal restructuring, the essence of which is to identify patterns in the internal binary data structure of an information resource by a quantitative criterion. The tool for data restructuring is a quantitative feature - a feature of the number of series of units. The analysis of the effectiveness of the application of the developed method of internal restructuring from the standpoint of increasing the data protection of an information resource in the statistical space is carried out. The coding tool uses a statistical approach based on the classical Huffman algorithm. The developed method of internal restructuring allows us to solve an urgent scientific and applied problem related to increasing the efficiency of statistical coding from the standpoint of reducing structural redundancy and increasing the level of data security of an information resource.